Waste management behavior of households in Klang Valley, Malaysia / Sabariah Yusoff and Shahariah Asmuni - Yusoff, Sabariah; Asmuni, Shahariah (Faculty of Business and Management, 2021)
Enhancing demand side management is among the focus of Malaysia in its effort to pursue green growth throughout 2016 to 2020. Per capita waste disposal in the country is 0.3 to 1.2 kg and only a mere 2% is recycled. There is huge potential for reducing solid wastes in the country through a more sustainable waste management approach such as reducing, recycling and proper disposal. This paper explores the result of a quantitative study conducted via a survey questionnaire on 118 households around Klang Valley. Applying the protection motivation theory, an ordinary least squares regression is applied to data to determine the significant factors affecting waste management behavior of households. Several elements of waste management behavior are investigated, such as waste avoidance, green purchases and reuse and recycle behavior. Results of study show that coping and threat appraisal processes significantly affect waste disposal and reuse and recycle behavior. For green purchasing and waste avoidance behavior, they are affected by coping appraisal but not threat appraisal process. The study suggests that if the government can promote the information on how severe contaminated environments can have on humans and their surroundings, it can lead to more responsible disposal of waste as well as can increase reuse and recycling activities of households. Apart from that, highlighting the positive impact an individual person’s action can bring to the environment may increase reuse and recycling, waste avoidance and disposal and green purchase activities of the society, particularly the households.